Assessment of the production potentials of Miscanthus on marginal land in China. (February 2016) - Xue, Shuai; Lewandowski, Iris; Wang, Xiaoyu; Yi, Zili
Abstract: Miscanthus is characterized by high biomass production potential and low input requirements and therefore considered a leading candidate for second-generation energy crops. Because China has limited agricultural land resources, development of its miscanthus-based bioenergy industry must rely on the use of marginal land. This study focuses on the assessment of the production potential of miscanthus on China's marginal land, which in this context is defined as land presently not used for agricultural production, residential purposes and other social uses. Geographic Information System (GIS) techniques and model simulation are adopted to identify the productive marginal areas for miscanthus and to estimate their biomass and bioenergy production potential. The results show that although a large marginal area of 17, 163.54×10 4  ha is available for producing miscanthus, due to the limitation of low winter temperatures and low precipitation levels in some areas, the total suitable marginal area is only 769.37×10 4  ha. The Monteith radiation yield model was used to determine the potential miscanthus yield in Chinese climatic conditions. The simulation gave actual harvestable yield levels on arable land of 18.1–44.2 t ha −1  yr −1 . Taking the environmental stresses of marginal conditions into account then gave an achievable miscanthus yield potential on marginal land of 2.1–32.4 t ha −1  yr −1 (average for the different marginal lands). Based on these achievable yield levels, the total biomass production potential on the entire marginal area is 13, 521.7×10 4  t yr −1 ; the bio-electricity generation and total greenhouse gas saving potential from these biomasses are 183.9 TW h yr −1 and 21, 242.4×10 4  t CO2  eq. yr −1, respectively. The spatial distribution of the suitable marginal areas shows that they are mainly concentrated in the central part of Northeast China and the Loess Plateau. Both regions are recommended as priority development zones for the Chinese miscanthus-based bioenergy industry.